Implementasi Ajaran Tri Kaya Parisudha dalam Pendidikan Karakter pada Generasi Metaverse - Ali Mustofa; Victor Novianto (Proceedings Series on Social Sciences & Humanities, 2022)
The development of the world towards the Metaverse greatly affects human life. In addition to having a positive impact, negative impacts are also unavoidable. The ease of accessing information through the internet is also very influential in lifestyle, especially for the younger generation. One way to fortify oneself from negative influences is to find in the Vedic scriptures, about character. This teaching is called Tri Kaya Parisudha or three core characters, namely: thinking well (manacika), saying good (wacika), and doing good (kayika). The character values developed for each core character are different. The core character includes the good values of positive thinking, religious character, and belief in the law of causality, the core character says good, includes values, tells the truth, while the good core character includes the values of compassion, honesty, caring for the environment, and discipline. The teaching of character education is carried out in an integrated manner in learning. By knowing, ensuring, and implementing the Tri Kaya Parisudha, young people can be wiser in everyday life.